PERSONAL IMAGE - Agus Hasan Pura A (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
lndividuals develop their personal image through interaction with other people or groups which they have relationships for years. Personal image is how a person would others to see her/him, which generally believed that people will try to develop their persona! image white competition increases especially in public sectors such as campaign of city mayor, election of house representative member, promotion, and election of dean- People will evaluate personal image through to what extent their behavior consistent with their own personal image. If they behavior is not consistent with their personal image, they wilt loss their credibility thus it will be difficult to rebuild their own personal image.